Genomic High-Resolution Profiling of Single CKpos/CD45neg Flow-Sorting Purified Circulating Tumor Cells from Patients with Metastatic Breast Cancer. (1st October 2014) - Neves, Rui P L; Raba, Katharina; Schmidt, Oliver; Honisch, Ellen; Meier-Stiegen, Franziska; Behrens, Bianca; Möhlendick, Birte; Fehm, Tanja; Neubauer, Hans; Klein, Christoph A; Polzer, Bernhard; Sproll, Christoph; et al.
Abstract: BACKGROUND: Circulating tumor cells (CTCs) are promising surrogate markers for systemic disease, and their molecular characterization might be relevant to guide more individualized cancer therapies. To enable fast and efficient purification of individual CTCs, we developed a work flow from CellSearch TM cartridges enabling high-resolution genomic profiling on the single-cell level. METHODS: Single CTCs were sorted from 40 CellSearch samples from patients with metastatic breast cancer using a MoFlo XDP cell sorter. Genomes of sorted single cells were amplified using an adapter–linker PCR. Amplification products were analyzed by array-based comparative genomic hybridization, a gene-specific quantitative PCR (qPCR) assay for cyclin D1 ( CCND1 ) locus amplification, and genomic sequencing to screen for mutations in exons 1, 9, and 20 of the phosphatidylinositol-4, 5-bisphosphate 3-kinase, catalytic subunit alpha ( PIK3CA ) gene and exons 5, 7, and 8 of the tumor protein p53 ( TP53 ) gene. RESULTS: One common flow-sorting protocol was appropriate for 90% of the analyzed CellSearch cartridges, and the detected CTC numbers correlated positively with those originally detected with the CellSearch system ( R 2 = 0.9257). Whole genome amplification was successful in 72.9% of the sorted single CTCs. Over 95% of the cells displayed chromosomal aberrations typical for metastatic breast cancers, and amplifications at the CCND1 locus were validated by qPCR. Aberrant CTCs from 2 patients harbored mutations in exon 20 of the PIK3CA gene. CONCLUSIONS: This work flow enabled effective CTC isolation and provided insights into genomic alterations of CTCs in metastatic breast cancer. This approach might facilitate further molecular characterization of rare CTCs to increase understanding of their biology and as a basis for their molecular screening in the clinical setting.